Sesquiterpene Lactones with Astrodaucane Skeleton from Astrodaucus orientalis - Hashempour, Hossein; Herfati, Farshid; Valizadeh, Hassan; Mahmoudi-Kordi, Fatemeh; Ebrahimi, Samad Nejad; Hamburger, Matthias; Farimani, Mahdi Moridi (Planta Medica, 2023)
Four sesquiterpene lactones, astrodaucanolide A – D (1–4) with unique structures, toghether with two known phenylpropanoid esters (5 and 6) were isolated from a flower extract of Astrodaucus orientalis. The structures were established by 1D and 2D NMR spectroscopy and high-resolution mass spectrometry (HRESIMS), and the absolute configuration of 1–4 was determined by electronic circular dichroism (ECD). Compounds 1–4 novel architecture represents a new class of sesquiterpenes with new skeleton. A putative biosynthetic pathway for their scaffold is proposed with a germacryl cation as the precursor. The suggested biosynthesis pathway is similar to that of eudesmane sesquiterpenes with a different direction of protonation which then leads to the new skeleton, named astrodaucane by the 1,2-methyl migration.
Keywords: Astrodaucus orientalis; Apiaceae; sesquiterpene lactone; Astrodaucane; Germacryl cation; Eudesmane